2012
DOI: 10.1016/j.ijrobp.2010.12.022
|View full text |Cite
|
Sign up to set email alerts
|

IMRT for Image-Guided Single Vocal Cord Irradiation

Abstract: Single vocal cord irradiation with IMRT resulted in good target coverage and provided significant sparing of the critical structures. This has the potential to improve the quality-of-life outcomes after RT and maintain the same local control rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Intriguingly, preliminary reports from a prospective study examining the feasibility of IMRT-based single vocal cord irradiation for T1a glottic tumors has demonstrated promising 2-year local control rates and a modest, transient decline in voice quality by voice handicap index. These findings illustrate the potential to improve voice outcomes by minimizing irradiation of the contralateral VC (3639). …”
Section: Discussionmentioning
confidence: 68%
“…Intriguingly, preliminary reports from a prospective study examining the feasibility of IMRT-based single vocal cord irradiation for T1a glottic tumors has demonstrated promising 2-year local control rates and a modest, transient decline in voice quality by voice handicap index. These findings illustrate the potential to improve voice outcomes by minimizing irradiation of the contralateral VC (3639). …”
Section: Discussionmentioning
confidence: 68%
“…Anderson Cancer Center revealed significantly reduced radiation dose to the carotid arteries compared with conventional lateral fields while maintaining target volume coverage [20]. Other study groups showed similar results [21,33]. Chera and Feigenberg et al challenge the interpretation of a new standard because of the risk of complication from dose heterogeneity [15,34].…”
Section: Discussionmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) offers the potential to spare surrounding tissues, e.g. carotid arteries or parts of the larynx [15-21]. Latter series only include few patients or consist of dosimetric comparison of different treatment techniques only.…”
Section: Introductionmentioning
confidence: 99%
“…High local control rates should shift focus onto reducing dose to surrounding normal structures since conventional therapy exposes organs-at-risk (contralateral vocal cord, arytenoids, low pharyngeal constrictors) to full dose. In fact, IMRT-based single cord irradiation strategies are currently being investigated [19]. Our initial dosimetric review indicates that our SBRT approach using sophisticated near real-time image guidance improves upon selective IMRT larynx treatment (manuscript submitted).…”
Section: Discussionmentioning
confidence: 99%